Antibiotic Use in Low and Middle-Income Countries and the Challenges of Antimicrobial Resistance in Surgery - Massimo Sartelli; Timothy C. Hardcastle; Fausto Catena; Alain Chichom-Mefire; Federico Coccolini; Sameer Dhingra; Mainul Haque; Adrien Hodonou; Katia Iskandar; Francesco M. Labricciosa; Cristina Marmorale; Ibrahima Sall; et al. (MDPI AG, 2020)
Antimicrobial resistance (AMR) is a phenomenon resulting from the natural evolution of microbes. Nonetheless, human activities accelerate the pace at which microorganisms develop and spread resistance. AMR is a complex and multidimensional problem, threatening not only human and animal health, but also regional, national, and global security, and the economy. Inappropriate use of antibiotics, and poor infection prevention and control strategies are contributing to the emergence and dissemination of AMR. All healthcare providers play an important role in preventing the occurrence and spread of AMR. The organization of healthcare systems, availability of diagnostic testing and appropriate antibiotics, infection prevention and control practices, along with prescribing practices (such as over-the-counter availability of antibiotics) differs markedly between high-income countries and low and middle-income countries (LMICs). These differences may affect the implementation of antibiotic prescribing practices in these settings. The strategy to reduce the global burden of AMR includes, among other aspects, an in-depth modification of the use of existing and future antibiotics in all aspects of medical practice. The Global Alliance for Infections in Surgery has instituted an interdisciplinary working group including healthcare professionals from different countries with different backgrounds to assess the need for implementing education and increasing awareness about correct antibiotic prescribing practices across the surgical pathways. This article discusses aspects specific to LMICs, where pre-existing factors make surgeons' compliance with best practices even more important.